Republic of Estonia : Reassessment Report on the Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2009)
This report provides a reassessment of fiscal transparency practices in Estonia in relation to the requirements of the IMF Code of Good Practices on Fiscal Transparency. It presents a description of practices prepared by IMF staff on the basis of discussions with the authorities and their responses to the fiscal transparency questionnaire, and drawing on other available information. The report presents an IMF staff commentary on fiscal transparency in Estonia. A summary of IMF staff assessments and comments on observance of good practices is also presented.